The environmental price of socio-economic development: Worldwide trends from 1990 to 2016 - VINTAR MALLY, Katja (European Journal of Geography, 2022)
Plans for achieving sustainable development around the world are based on the assumption that socio-economic progress can be ensured only by staying within the carrying capacity of the environment, which has already been exceeded in a number of areas. In this paper the concepts of human development and ecological footprint have been combined in order to shed light on the current state and trends over time. Using available data for the human development index and the ecological footprint, 175 countries were included in the analysis of the current state (based on data from 2016), while 121 countries were analysed in the study of trends from 1990 to 2016. Based on their degree of success or failure in approaching decoupling targets, the countries were further classified into three types. All countries have shown progress in human development, which has been accompanied on a global scale by a large increase in environmental pressures, and this is still reflected in the high correlation of the human development index and the ecological footprint per capita. However, for only 38% of countries could it be concluded that socio-economic progress in the period 1990-2016 was achieved while reducing the per capita consumption of natural resources and ecosystem services.